2007
DOI: 10.1038/nature06460
|View full text |Cite|
|
Sign up to set email alerts
|

Two stellar components in the halo of the Milky Way

Abstract: The halo of the Milky Way provides unique elemental abundance and kinematic information on the first objects to form in the Universe, and this information can be used to tightly constrain models of galaxy formation and evolution. Although the halo was once considered a single component, evidence for its dichotomy has slowly emerged in recent years from inspection of small samples of halo objects. Here we show that the halo is indeed clearly divisible into two broadly overlapping structural components-an inner … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

126
795
14
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 619 publications
(946 citation statements)
references
References 55 publications
(81 reference statements)
126
795
14
4
Order By: Relevance
“…To calibrate the measured difference in the mass of white dwarfs forming today in these two Next, using the same stellar evolution models that were applied to the globular cluster Messier distinct in their abundances and kinematics 24,25 . The latest SPH + N--body simulations of the formation of stellar halos are also finding evidence for a dual origin to the halo.…”
mentioning
confidence: 99%
“…To calibrate the measured difference in the mass of white dwarfs forming today in these two Next, using the same stellar evolution models that were applied to the globular cluster Messier distinct in their abundances and kinematics 24,25 . The latest SPH + N--body simulations of the formation of stellar halos are also finding evidence for a dual origin to the halo.…”
mentioning
confidence: 99%
“…The break in the stellar density profile could also be an indication that the Milky Way has a "dual stellar halo," containing populations of different origins (Carollo et al 2007(Carollo et al , 2010Beers et al 2012). Simulations predict that the stellar halo is composed both of accreted stars and stars that form in situ (e.g., Zolotov et al 2009;Font et al 2011;McCarthy et al 2012;Tissera et al 2012;Cooper et al 2015).…”
Section: Dual Stellar Halo: In Situ Star Formationmentioning
confidence: 99%
“…Much of the discussion in recent years has been focused on ways to quantify the amount of different stellar populations in a way to ascertain the importance of the merging history in the formation of the Milky Way. The works of Carollo et al (2007Carollo et al ( , 2010, for example, have shown observational evidence that there is an outer stellar halo, which is dominant at galactocen-⋆ E-mail: khawkins@ast.cam.ac.uk tric distances larger than 15 kpc, mostly formed from accreted sub-units and an inner stellar halo, confined to galactocentric distances less than 15 kpc, which seems to be rather smooth, with no predominant sub-unit like the outer halo. However, these results are still debated (see discussion in Ivezić, Beers & Jurić 2012;Schönrich, Asplund & Casagrande 2011).…”
Section: Introductionmentioning
confidence: 99%